2000
DOI: 10.1089/088922200309377
|View full text |Cite
|
Sign up to set email alerts
|

Highly Variable Sequences in theenvV3 Region of HIV Type 1 Distributing among Thai Carriers from 1995 to 1997

Abstract: The amino acid sequences of the Env V3 region of HIV-1 subtype E in Thailand were highly variable in the samples obtained from 1995 to 1997, compared with the previously reported sequences in samples obtained from 1990 to 1993. The sequences of the V3 region in the samples from five provinces in Thailand revealed that the variability was much higher in the samples from Bangkok and Ubonrachathani than in those from Chiangmai, Prathumthani, and Trang. There was no apparently different level of diversity at the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…First, it was noted that the withinsubtype interhost genetic divergence had increased significantly compared to that noted in earlier surveys (9,10,17,(22)(23)(24)(25). Second, the barriers that maintained the segregation of subtypes on the basis of risk factors started to efface; the representation of CRF01_AE among IDUs increased, especially among new infections (26), to the point where CRF01_AE accounted for 80 to 90% of the cases in Bangkok and the northern province of Chiang Mai (27,28).…”
mentioning
confidence: 95%
“…First, it was noted that the withinsubtype interhost genetic divergence had increased significantly compared to that noted in earlier surveys (9,10,17,(22)(23)(24)(25). Second, the barriers that maintained the segregation of subtypes on the basis of risk factors started to efface; the representation of CRF01_AE among IDUs increased, especially among new infections (26), to the point where CRF01_AE accounted for 80 to 90% of the cases in Bangkok and the northern province of Chiang Mai (27,28).…”
mentioning
confidence: 95%
“…The initial HIV-1 CRF01_AE isolates obtained from asymptomatic carriers in Thailand between 1990 and 1992 were remarkable for their genetic homogeneity. Recently, we showed that the amino acid sequences in the env V3 region of HIV-1 CRF01_AE in Thailand were highly variable in samples obtained from 1995 to 1997, 9 compared with the previously reported sequences in samples obtained from 1990 to 1992. The sequences of the V3 region in the samples from five provinces in Thailand revealed that the variability was much higher in the samples from Bangkok and Ubonrachathani than those from Chiangmai, Prathumthani, and Trang.…”
mentioning
confidence: 55%
“…9 The patient's peripheral blood mononuclear cells (PBMCs) were separated on Ficoll-Paque and cultured in RPMI-1640 medium containing 50 units/ml of interleukin-2 (IL-2) (Boehringer-Mannheim, Mannheim, Germany), 10% fetal bovine serum (FBS), and antibiotics. Aliquots of 2 3 10 5 PBMCs were cocultured with 6 3 10 5 phytohemagglutinin (PHA) (5 mg/ml)-stimulated healthy donor-derived PBMCs in 24-well microplates in a total volume of 2 ml/well for 7 days.…”
mentioning
confidence: 99%
“…The primers used were previously described: for env V3, MK603 and CO602 followed by EB2 and EC2 [18]; and for vpu, Tat-1 and Vpu-2 followed by Tat-3 and Vpu-4 [13]. The PCR products were subjected to direct sequencing using ABI version 3.7 [18].…”
Section: Phylogenetic Tree Analysismentioning
confidence: 99%
“…The primers used were previously described: for env V3, MK603 and CO602 followed by EB2 and EC2 [18]; and for vpu, Tat-1 and Vpu-2 followed by Tat-3 and Vpu-4 [13]. The PCR products were subjected to direct sequencing using ABI version 3.7 [18]. The phylogenetic trees of these sequences were constructed by the neighbor joining method with ClustalW program (1.82) under the default parameters on the ClustalW web server (http://srs.ebi.ac.uk).…”
Section: Phylogenetic Tree Analysismentioning
confidence: 99%